Pengaruh PDRB, Pendidikan dan Pengangguran Terhadap Kemiskinan di Provinsi Bali - Astrini, Myanti; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Poverty is a situation where people are not able to meet the needs and the good life, such as food, cloth, and home. Poverty can also lead to ignorance due to lack of access to the education they receive. Bali is one of the famous tourist destinations in Indonesia as seen from the cultural arts. In this study discusses the influence of regional gross domestic product, education, and unemployment on poverty in the province of Bali. The discussed issue is about the effect of simultaneous or partial influence of regional gross domestic product, education, and unemployment on poverty in the province of Bali, and the dominant variable on poverty in the province of Bali. The analysis technique used in this study is multiple regression analysis, the classical assumptions, and analyzes the influence of simultaneously (F) and partial (t). Results of the analysis based on four variables that indicate the results of the F test simultaneously influence between GDP, education and unemployment on Poverty in the province of Bali. The t test showed that the negative effects and no significant correlation between GDP and poverty caused by the unequal distribution income of Balinese citizen. Education is partially negative and significant effect on poverty due to the increase in the literacy rate will reduce illiteracy. And unemployment is partially positive and significant effect because the lower unemployment then poverty will decline.
Keywords: Regional Gross Domestic Product; education; unemployment; poverty